The Tradition of Short Story in Arabic Literature - Muhammad Javed (بازیافت, 2019)
Arabic literature is one of the oldest as well as the richest literatures of the world. It dates back to the pre Islamic period. It was basically in verse form and was transmitted orally from one generation to the other. Since the Arab land was barren and short of sources, the Arabs had to struggle hard to make both ends meet. It is in this perspective that oral tradition of Arabic literature flourished. It contained all tinge of literature though mainly in verse. The Arabs got acquainted with the form of story when stories from other languages were translated in Arabic. Modern day concept of short story is novel to Arabic literature. The Arab writers took fancy of it and first translated western short stories into Arabic and then began producing original ones. This article traces the tradition of fiction in Arabic literature.